(3MSf GdJUQa HTQM GdJYQas - (3CHh GdMSf Ydj ESeGYjd Hf jhSa Gdbhfhi GdTGaYjs; (3eMeO Hf EHQGgje Hf jYbhH GdcdGHGPj GdHNGQj, CHh HcQ,J (B380 (3g` s ((3CMeO Hf Ndjd GdeOjfi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi Ydi LRjd CaVGdg hGdUdGI hGdSdGe YdiSjOfG eMeO hSde agPg YLGdI JMQi eLQi GdTQM dHYV GdahGFO GdJi jTJed YdjgG cJGH GdJYQa dePgH Cgd GdJUha s
(3BNQgG (B:s
(3gPG BNQ GdTQM GdeSei HMSf GdJUQa ai TQM GdJYQja s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B212s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B419s
Keywords: (3GdJUha hGdBOGH GdTQYjIs